Perda e luto: Vivências de mulheres que interromperam a gestação por malformação fetal letal - Consonni, Elenice Bertanha [UNESP]; Lopes Petean, Eucia Beatriz (FapUNIFESP (SciELO), 2013)
The scope of this study was to investigate the grieving experiences of women who terminated pregnancies under judicial authorization, due to life-incompatible fetal malformation. Ten women attended in the Fetal Medicine Department of Botucatu Clinical Hospital participated in the study. Data collection was conducted by means of semi-structured interviews forty days after termination. The interviews were recorded and transcribed in full, with the data analyzed from the thematic content analysis perspective. The results revealed that the mothers sought explanations and meanings for the loss, with religious responses and self-blame being very frequent. The reports were marked by feelings of sadness, longing and sensations of emptiness due to the loss of the child, revealing the need of the mothers to dwell on the issue. The mothers were and continued to be linked to their children; the termination of the pregnancy, although being a choice to minimize the pain of an inevitable loss, did not spare the women from experiences of great suffering. The study includes input for the discussion and planning of health approaches and care for women who terminate their pregnancy due to lethal fetal malformation, by means of judicial authorization.
Loss and grieving: The experiences of women who terminate a pregnancy due to lethal fetal malformations
Keywords: Fetal malformation; Grieving; Termination of pregnancy